2001
DOI: 10.1108/eum0000000006494
|View full text |Cite
|
Sign up to set email alerts
|

Convenience or content: a study of undergraduate periodical use

Abstract: Full-text periodical databases have changed how students access research materials. Many librarians fear that students favor the convenience of full-text databases over more valuable information found in print periodical literature. To what extent is this true? A study was undertaken at Oakland University to determine how well students mastered the retrieval process for print and full-text articles, and to gather their opinions on the value of both formats. A pre-/post-test instrument was administered to stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…19,20 In a study of students enrolled in a fresh man-level writing course, Shawn V. Lombardo and Kristine S. Condic found that more than 35 percent of undergradu ates ignored citations to articles available in the library in print format in favor of citations to online articles. 21 Further, onequarter of the library users surveyed at the University of North Carolina indi cated that they would never use print re sources under any circumstances. 22 Stu dents want to complete their research with a minimum of time and effort and, for many of them, the library's electronic resources are the only answer.…”
mentioning
confidence: 99%
“…19,20 In a study of students enrolled in a fresh man-level writing course, Shawn V. Lombardo and Kristine S. Condic found that more than 35 percent of undergradu ates ignored citations to articles available in the library in print format in favor of citations to online articles. 21 Further, onequarter of the library users surveyed at the University of North Carolina indi cated that they would never use print re sources under any circumstances. 22 Stu dents want to complete their research with a minimum of time and effort and, for many of them, the library's electronic resources are the only answer.…”
mentioning
confidence: 99%
“…Sadly, I know of several faculty who continually complain of their students' poor research skills yet do not ask for research instruction assistance nor compel their students through well-designed assignments and grading techniques. As previously mentioned, most college students welcome being taught information literacy and research skills (Gibbons, 2007;Lombardo & Condic, 2001;Messineo & DeOllos, 2005;Serotkin, 2005). The challenge comes from attempting to impart advanced skills and hard-to-grasp principles in what is many times a single meeting (Serotkin, 2005).…”
Section: Libraries Customer Service and Instructionmentioning
confidence: 95%
“…The role of user education and customer service (Connaway & Radford, 2007Lombardo & Condic, 2001;How academic, 2002;Serotkin, 2005) is paramount to students using library-based virtual resources. In this context, Brand Theater is nothing more than a learner-centered strategy whose major tenants fit well into millennial pedagogy and information literacy instruction.…”
Section: Libraries Customer Service and Instructionmentioning
confidence: 99%
“…15 At Oakland University, Shawn Lombardo and Kristine Condic studied freshman rhetoric students in their efforts to locate periodicals and found that students valued the convenience of full-text resources over print resources. 16 Serials displays have been discussed in the literature. Nancy Lee Shires and Lydia Olszak provided checklists for effective OPAC screens and discussed the criteria for effective OPAC displays.…”
Section: Literature Reviewmentioning
confidence: 99%